Employee perception level towards effectiveness of ACD program for SKG9 & SKG10 in Petroleum Engineering Division, Petronas Carigali Sdn.Bhd. / Hazman Hasim - Hasim, Hazman (Faculty of Business and Management, 2010)
This study is focus on the effectiveness & performance issues at PETRONAS Carigali Sdn. Bhd., Petroleum Engineering Capability Management Department (PEK) which has potential to affect company’s performance. The main objective of this project paper is to determine whether the program had run smoothly, achieve it target while rate the satisfaction & confidence level on employees level either this program help them to improve their performance and can help them to achieve their career goals. The research is focusing on Accelerated Capability Development (ACD) process at PETRONAS Carigali Sdn. Bhd., Petroleum Engineering Division. The theoretical framework of this study consists of dependent variable and independent variables. The sample size of this study was 148 of executive in PETRONAS CARIGALI, PETROLEUM Engineering Division. Data was obtained using primary data. Respondents were required to answer the questionnaires that included the statements of each variable. Once the necessary data was collected, the data was analyzed and summarized in a readable and easily interpret form. The Statistical Package for the Social Science (SPSS) version 14.0 was used to summarize the data. The results are in form of reliability testing, descriptive statistic, ANOVA, T-test and correlation. Based on this research, the result indicates that training are the factors that have a moderate relationship with employee performance and development while assessment and coaching give the weak impact. The conclusion of the study is the outcome of the survey analysis and findings. Based on the findings, some recommendations have been suggested in order to improve the understanding on how PETRONAS CARIGALI especially Petroleum Engineering Division can make to improve the perception of its employee in ACD program.